2014
DOI: 10.1097/bot.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Effects of Off-Axis Insertion of Locking Screws

Abstract: These findings indicate that cross threading may not be biomechanically advantageous and may change screw mode of failure. Based on these findings, screws inserted to 3 degrees or higher would reduce the bending moment at failure to approximately 50% of an orthogonally inserted screw.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…As previously shown in quasi‐static tests, tilted fixed angle locking screws failed at a low bending moment and were therefore not considered in the current study . Loosening of fixed angle locking screw heads is mainly induced by misinsertion of the screws in a tilted position, not orthogonal to the hole threads, where only a cross‐threading but no locking of the screw head occurs .…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…As previously shown in quasi‐static tests, tilted fixed angle locking screws failed at a low bending moment and were therefore not considered in the current study . Loosening of fixed angle locking screw heads is mainly induced by misinsertion of the screws in a tilted position, not orthogonal to the hole threads, where only a cross‐threading but no locking of the screw head occurs .…”
Section: Discussionmentioning
confidence: 90%
“…Failure mode depends on the head locking mechanism: In the current study, all locking screws failed at the shaft‐head junction. Breakout of the head thread, being described as failure mode of other polyaxial locking systems, using a hoop of softer grade II titanium or a star petal interface for head locking, was not observed, indicating a lasting head locking mechanism in the allowed inclination range of the variable angle locking screws . Overloading the end cap polyaxial locking system, which is based on frictional coupling, exhibited a slippage of the screw head under the end cap at a failure moment comparable to locked fixed angle locking screws but with subsequent relocking when the moment was decreased …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a previous study, Kä ä b et al [24] investigated locked screw-plate constructs and observed a significant drop in stability with screw axis deviation bigger than 58. Similarly, Cartner et al [25] concluded that screws inserted to 38 or higher off-axis angulation would reduce their bending moment at failure to approximately 50% of a properly inserted screw, and primarily fail through disengagement of the locking mechanism. The higher impact of 28 screw misangulaton on implant stability in our study probably results from the more coarse characteristics of the screwhead and hole threads.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple insertion axes were used to test the effect on various degrees of cross-threading on bending strength 38 . â As insertion angle increased, the bending strength decreased.…”
Section: Basic Sciencementioning
confidence: 99%